Mapping Climate-related Disaster Preparedness in Decentralized Ternate as Global Climate Change Adaptation - Dewa Ayu Putu Eva Wishanti; Joko Purnomo; Wishnu Mahendra Wiswayana (Parahyangan Center for International Studies, 2021)
Climate change adaptation is globally arranged in many agreements. Those regimes realize the importance of small islands and vulnerable community as the entities at prime risk. However, as climate change progresses slowly, developing countries do not put this as a priority compared to other natural calamities like earthquake of volcanic eruption. Ternate authority as a government of sub-national small island is prone to climate hazard, but practically not prepared to defend the island against climate disaster. Despite receiving an award as a climate-resilient city, a wider governance aspect is left incapable to build an early initiative to construct a solid governance mode to manage its vulnerability. Through a set of indicators of policy approach, institutional capability, and social capability, this research finds that local governance and local politics in small island government is not supporting the establishment of an adaptable government, particularly on the context of decentralization. Technical capabilities in Ternate is present as a best practice to respond to volcanic eruption and tsunami, but not to the threat of climate change. Eventually, the case of Ternate highlights the importance to position subnational small islands according to its unique feature as a frontline to climate change adaptation, both in global and national context. Decentralization of governance does not automatically intensify the initiative of Ternate government to adapt with climate change imperatives.